EFFECT OF ERYTHROPOIETIN ADMINISTRATION ON THE AMOUNT OF SPERMATOGONIUM, SERTOLI CELL, AND LEYDIG CELL ON RATS TESTIS (WISTAR STRAIN) AFTER VAS DEFERENS LIGATION RELEASED - Negara, Muhammad Surya; Soetojo, Soetojo; Soebadi, Doddy M (Indonesian Journal of Urology, 2019)
Objective: To determine the effect of Erythropoietin (EPO) on the number of spermatogonia, Sertoli cells, and Leydig cells in white rats wistar strain testis after the release of ligation vas deferens. Material & Methods: Twenty-four Wistar strain rats were grouped into 4 groups. The control group only performed an orchiectomy for testicular examination, ligation group vas deferens only, group performed release ligation of vas deferens, and group performed release ligation of vas deferens and given EPO injection with dose of 1000 iu/kg BW intraperitoneally for 1 week (3x/week). Observation of spermatogonium, Sertoli cells and Leydig cells by counting the amount on the 5 cross sections of the seminiferous tubules using a 400x light magnification microscope with Haematoxylin Eosin staining. Results: Ligation of vas deferens can significantly decreased the number of spermatogonia and Sertoli cells (p<0.05). In Leydig cells there was no significant difference in numbers after ligation of vas deferens (p>0.05). Release of vas deferens ligation turned out to be no significant amount difference in spermatogonia, Sertoli cells, and Leydig cells with ligation of vas deferens group. Similarly, the treatment of ligation vas deferens release and an EPO injection for 1 week was also no significant difference in number compared to the ligation release group of vas deferens. Conclusion: The number of Sertoli cells, Leydig cells, and spermatogonia in the ligation release group of vas deferens and given EPO for 1 week had the same number with the ligation release group vas deferens.